Good and Bad Characters: A Poetic Difference - Brenes, Carmen Sofía (2022)
This article reflects on the notion of good and bad characters in a fictional world. The study is done from a humanistic perspective and considers the poetic proposal of Juan José García-Noblejas (1982) and Paul Ricoeur (1987). The paper suggests that a character is good as long as it serves the world of fiction in which it is, whereas the world of fiction is good - in the sense of complete - insofar as it is able to "do justice" to the part of human life it represents.